DETEKSI KECURANGAN LAPORAN KEUANGAN MENGGUNAKAN BENEISH M – SCORE DAN PREDIKSI KEBANGKRUTAN MENGGUNAKAN ALTMAN Z – SCORE (Studi Empiris pada Perusahaan yang Termasuk dalam Indeks LQ – 45 Tahun 2016 – 2018) - Caterina Kesuma Dinasmara; Agustinus Santosa Adiwibowo (Diponegoro Journal of Accounting, 2020)
Financial statements can be the one of the source of financial information in a company. Fraud can be seen through financial reports, which can be interpreted as acts intended to get personal benefit or in a group that can harm other parties directly or indirectly, which is usually done by parties from within or outside the organization and is an illegal activity. Through the company's financial statements can be seen the financial condition of a company. If the company experiences economic difficulties, the company is unable to pay off its obligations or debt. If the company is exposed to financial distress, the company is considered to have failed in their business. This study was conducted with the aim of finding out companies listed on the Indonesia Stock Exchange (IDX) and those included in the LQ-45 index who were manipulating on their financial statements and who had financial difficulties reflected in the financial statements presented.             The sample used in this study were 24 companies listed on the Indonesia Stock Exchange (IDX) and included in the LQ-45 index in 2016 - 2018. The type of data used in this study is secondary data, which is in the form of company annual reports. This study uses quantitative descriptive methods to analyze data. Beneish M - Score is used to detect financial statement fraud and Altman Z - Score is used to predict bankruptcy in companies.            The results of this study indicate that in 2016 there were 42% of companies classified as manipulators, in 2017 there were 33% of companies classified as manipulators, and in 2018 there were 29% of companies classified as manipulators. In addition, in 2016 there were no companies experiencing financial difficulties or going bankrupt and in 2017 and 2018 there were 1 (one) or 4% of companies experiencing financial difficulties or who were going bankrupt.